Combining two parasitoids (Asecodes hispinarum and Tetrastichus brontispae) for biological control of coconut leaf beetle - Qikai Zhang; Bin Jiao; Hui Lu; Jihong Tang; Xu Zhang; Baoqian Lyu (Biological Control)
The coconut leaf beetle (CLB), Brontispa longissima, is a major threat to coconut production worldwide, causing widespread and important losses throughout the tropics. Two eulophid parasitoids, larval parasitoid Asecodes hispinarum and pupal parasitoid Tetrastichus brontispae, are the dominant natural enemies of CLB. However, the combined use of these species for biocontrol has not been systematically explored. We analyzed the interactions of A. hispinarum and T. brontispae and evaluated possible deployment strategies by determining the outcomes of releases under realistic agricultural conditions. Our laboratory studies showed that the concurrent release of the two parasitoid species did not reduce either species lifespan or reproductive output, and it significantly enhanced the impact on CLB. A 3:1 ratio of A. hispinarum to T. brontispae, a 10:1 parasitoid-to-pest ratio, and a regimen of five consecutive monthly releases proved to be the most effective strategy in the laboratory. When this combined release approach was used in field trials over a two-year period, there were significant reductions in pest densities and higher parasitism rates than single-species releases. This study highlights the potential of integrating multiple parasitoid species to improve biological control programs.